2020
DOI: 10.2478/ast-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Production Usage, and Potential Public Health Effects of Aluminum Cookware: A Review

Abstract: AbstractThe ingestion of aluminum from food containers such as cookware, cans, utensils and wrappings and its subsequent release into the environment is a growing public health concern. Aluminum is widely used in manufacturing cookware due to its malleability, high heat conductivity, light weight, durability, availability and affordability. This paper therefore gives a review of most relevant literatures on the benefits and risks of the various types of aluminum cookware in use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Cottage industries constitute a sub-category of the informal sector, in which the use of lead, and concomitant lead exposure, is particularly pernicious and intractable. A small number of studies undertaken during recent years have shone a light on potential lead exposure from the operation of small backyard foundries to smelt waste aluminium and forge artisanal pots [4][5][6][7]10]. Concerns relate to lead exposure amongst cookware makers during the production process, end-users from contamination of cooked or stored food, and from lead contamination of the local environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cottage industries constitute a sub-category of the informal sector, in which the use of lead, and concomitant lead exposure, is particularly pernicious and intractable. A small number of studies undertaken during recent years have shone a light on potential lead exposure from the operation of small backyard foundries to smelt waste aluminium and forge artisanal pots [4][5][6][7]10]. Concerns relate to lead exposure amongst cookware makers during the production process, end-users from contamination of cooked or stored food, and from lead contamination of the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…1) [4,5]. The process of melting aluminium waste and crafting the pots is usually undertaken by a pair of individuals, or in small groups in a home setting [5,6]. The work is laborious, and holds a risk of burn and other injuries, as well as exposure to air, dust and soil pollution.…”
Section: The Production Of Artisanal Aluminium Cookware In African Sementioning
confidence: 99%
“…Cookwares affect the nutritional composition of the food, both positively and negatively. Different metal cookwares can cause metal or trace metals toxicity (Dan and Ebong, 2013 (Alabi and Adeoluwa, 2020). All these cookwares have their own advantages and disadvantages in terms of durability, convenience, and cost (Table-4).…”
Section: Cookwares: Types and Effects On Nutritional Valuesmentioning
confidence: 99%
“…Studies have demonstrated that when metallic cookware comes in contact with food, migration of trace elements into food occurs [7] [8] [9] which poses a significant impact on human health. Although trace levels of some metals, such as Cr, Fe, Cu are vital for normal body functioning, excessive intake of such metals can be very harmful to health [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that ingestion of mercury, lead, arsenic and cadmium resulted in more than one million cases of ill health and more than 56,000 deaths, of which, over half (54%) were due to lead, 22% and 20% from methylmercury and arsenic respectively and 1% from cadmium [8]. The contamination of food with metals has been worsened by the use of locally fabricated cookware items manufactured from scrap metal by local artisans [7].…”
Section: Introductionmentioning
confidence: 99%